Do the Long-Term Unemployed Benefit from Automated Occupational Advice during Online Job Search? - Michèle Belot; Philipp Kircher; Paul Muller (Institute of Labor Economics (IZA), 2022)
In a randomized field experiment, we provide personalized suggestions about suitable alternative occupations to long-term unemployed job seekers in the UK. The suggestions are automatically generated, integrated in an online job search platform, and fed into actual search queries. Effects on the primary pre-registered outcomes of “finding a stable job” and “reaching a cumulative earnings threshold” are positive, are significant among those who searched at least once, and are more pronounced for those who are longer unemployed. Treated individuals include more occupations in their search and find more jobs in recommended occupations.
Keywords: D83; J62; C93; 330; online advice; job search; long-term unemployment; occupational mobility; field experiment